The Relationship Between Emotional Intelligence, Interpersonal Communication, Work Motivation, and Organizational Citizenship Behaviour of Public Junior High School Teachers - Indah Kurniasih; Aslamiah Aslamiah; Ahmad Suriansyah (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study aims to examine the levels and interrelationships among emotional intelligence, interpersonal communication, work motivation, and Organisational Citizenship Behaviour (OCB) among teachers at State Middle Schools in East Banjarmasin District. Employing a quantitative, descriptive-correlational design, the study involved 149 respondents selected through proportional random sampling from a total population of 237 teachers across seven schools. Data were collected using validated and reliable questionnaires and analyzed using descriptive statistics, classical assumption tests, multiple linear regression, path analysis, and the Sobel test. The results reveal significant direct effects of emotional intelligence (β = 0.260), interpersonal communication (β = 0.256), and work motivation (β = 0.310) on OCB. Emotional intelligence (β = 0.363) and interpersonal communication (β = 0.326) also significantly Influence work motivation. Furthermore, indirect effects were observed from emotional intelligence to OCB via work motivation (β = 0.112), and from interpersonal communication to OCB via work motivation (β = 0.101). The findings indicate that emotional intelligence and OCB are in the high category, while interpersonal communication and work motivation are in the moderate category. The study underscores the mediating role of work motivation in enhancing OCB and suggests that strengthening emotional and interpersonal competencies may promote positive organizational behaviour among teachers.